Reading Comprehension and Literacy Instruction for Students with Autism Spectrum Disorder - Ali Eissa Saad, Mourad (Technium Social Sciences Journal, 2022)
This research focuses on strategies for reading comprehension and engagement for students with ASD. There are few studies about the reading comprehension and word decoding of students with autism. Research indicates that only two studies investigated strategies to improve reading comprehension among these students. For example, a study of Reading Comprehension Profiles of High-Functioning Students on the Autism Spectrum (2012) found that using anaphoric cueing or asking students to define pronouns after they have been used in reading has been proven effective in improving reading comprehension. In another study, Children With Autism Spectrum Disorder and Literacy Instruction: An Exploratory Study of Elementary Inclusive Settings (2001), researchers found that reading comprehension improved when general education students were taught to use reciprocal questioning. This type of questioning allows students to ask the teacher questions about the reading so that students can demonstrate understanding. Further, using this strategy with general education students increased the number of questions generated, the responses to questions generated, and the responses to questions when using a story map.